(untitled) (Journal of the College of Basic Education, 2022)
The effectiveness inhibitory to extract alcohol for the leaf and flower to plant sage Salvia pratensis each of Staphylococcus aureus, streptococcus epidermidis, Salmonella typhi, Pseudomonas aeroginosa, Escherichia coli, Aspergillus niger and Candida albicans whom had any inhibition to aqueous extracts of the parts itself species bacterial and fungal. The study also demonstrated that the extract of plant containing compounds chemical such as tannins, Alkaloids, Flavonoieds, and saponins, which owns effectiveness of medical. The MIC, MBC and inhibition zones for crud extract were determinated for microbial agents.